2020
DOI: 10.1175/jcli-d-19-0993.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Future Change of Global Monsoons Projected by CMIP6 Models

Abstract: Projecting future change of monsoon rainfall is essential for water resource management, food security, disaster mitigation, and infrastructure planning. Here we assess the future change and explore the causes of the changes using 15 models that participated in phase 6 of the Coupled Model Intercomparison Project (CMIP6). The multimodel ensemble projects that, under the shared socioeconomic pathway (SSP) 2–4.5, the total land monsoon rainfall will likely increase in the Northern Hemisphere (NH) by about 2.8% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
147
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 38 publications
13
147
1
1
Order By: Relevance
“…The results based on the ensemble mean of ALL-GCMs are in agreement with the recent studies based on CMIP6-GCMs (Z. Chen et al, 2020;Cook et al, 2020;Wang et al, 2020). The projections based on the multimodel ensemble mean of GCMs are considerably influenced by a few GCMs that are highly sensitive to convective precipitation in response to warming .…”
Section: Evaluation Of Cmip6-gcms and Causes Of The Wet Summer Monsoosupporting
confidence: 89%
See 3 more Smart Citations
“…The results based on the ensemble mean of ALL-GCMs are in agreement with the recent studies based on CMIP6-GCMs (Z. Chen et al, 2020;Cook et al, 2020;Wang et al, 2020). The projections based on the multimodel ensemble mean of GCMs are considerably influenced by a few GCMs that are highly sensitive to convective precipitation in response to warming .…”
Section: Evaluation Of Cmip6-gcms and Causes Of The Wet Summer Monsoosupporting
confidence: 89%
“…Z. Chen et al (2020) and Wang et al (2020) found an increase in the Indian summer monsoon precipitation under the warming climate based on CMIP6-GCMs. However, these recent studies (Z.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The changes in spatial pattern of monsoon precipitation has been attributed to the shifts of tropical circulation (Chadwick et al, 2013; Held & Soden, 2006; Monerie et al, 2020; Rowell & Chadwick, 2018). Wang et al (2020) pointed out that two greenhouse gas (GHG)‐induced thermodynamic effects, i.e., the increase of specific humidity and the increase of atmospheric stability due to top‐heavy heating, tend to offset each other; on the other hand, the GHG‐induced horizontally differential warming results in the robust “NH‐warmer‐than‐SH” and “land‐warmer‐than‐ocean” patterns, as well as an “El Niño–like warming” pattern, driving circulation change (the GHG‐induced dynamic effect) that plays a fundamental role in shaping the spatial patterns of the GM precipitation changes.…”
Section: Introductionmentioning
confidence: 99%